2020
DOI: 10.1039/d0se00687d
|View full text |Cite
|
Sign up to set email alerts
|

New insights into phenazine-based organic redox flow batteries by using high-throughput DFT modelling

Abstract: DFT calculations reveal interesting structure–property relationships of the redox potentials of phenazines in non-aqueous media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 65 publications
2
77
0
Order By: Relevance
“…The main goal of this contribution is the establishment and validation of a standard procedure for the computational prediction of redox potentials of organic molecules undergoing a proton-coupled electron transfer. One of the main motivations for benchmarking such predictions is the computational screening of the vast chemical space of organic molecules to identify electrolytes for redox flow batteries (RFBs) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At some point in any computational workflow for materials discovery, one needs a reliable method to predict with reasonable accuracy and moderate computational cost the properties of an already pre-selected candidate pool.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this contribution is the establishment and validation of a standard procedure for the computational prediction of redox potentials of organic molecules undergoing a proton-coupled electron transfer. One of the main motivations for benchmarking such predictions is the computational screening of the vast chemical space of organic molecules to identify electrolytes for redox flow batteries (RFBs) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At some point in any computational workflow for materials discovery, one needs a reliable method to predict with reasonable accuracy and moderate computational cost the properties of an already pre-selected candidate pool.…”
Section: Introductionmentioning
confidence: 99%
“…ONPZ is considered a promising anode redox-active candidate for RBFs containing phenazine derivatives. 18 Additionally, most models were able to predict the correct relative order of compounds with respect to the redox potential, clustering potential cathode redox-active candidates in the negative region, and potential anode redox-active candidates in the region close to zero. It can be seen that the promising cathode redox-active species contain electron-donating groups (i.e., NH2), whereas promising anode redox-active species contain electron-withdrawing groups (i.e., CN, NO2).…”
Section: Identification Of the Promising Redox-active Candidatesmentioning
confidence: 99%
“…Data used in this study was obtained from the work reported by Mavrandonakis and coworkers. 18 The redox potentials of 189 phenazine derivatives in DME were provided in that work. These potentials were computed using DFT.…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Different families of organic molecules have been reported, including quinones, [8,9] viologens, [10] aza-aromatics, [11] ferrocene, [10c, 12] nitroxide radical species, [13] and azobenzene. [14] Phenazine and its derivatives, [15] which have been widely used as broad-spectrum antibiotics, [16] are good candidates for negolytes in AORFBs,owing to their low redox potentials and capability to accommodate two-electron transfers.However,the reported research of aqueous soluble redox-active phenazines for AORFBs is rather limited. The pioneering work reported by Schubert et al investigated the combined phenazine-TEMPO molecule through triethylene linker that exhibited reversible redox property but poor solubility in water.…”
Section: Introductionmentioning
confidence: 99%